Vince Flynn Denied access [compact disc, unabridged] - Bentley, Don; Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2025)
With the CIA's Moscow Station now paralyzed by a catastrophic intelligence failure, interim director Thomas Stansfield seeks help from Mitch Rapp, a newly minted assassin in the secretive Orion program. But Rapp has problems of his own: when his Swiss girlfriend Greta's grandfather receives a box containing the head of a former Cold War comrade along with a note promising that Greta's head will be next, Rapp finds himself on the frontlines in a war between the American and Russian intelligence services.